Determinants of Students’ Academic Honesty in the Context of AI-Based Learning Tools - B.M.A.S. Anaconda Bangkara (International Journal Labs, 2025)
The current technological advances are indeed something to be grateful for, even though they can also cause various problems. One area facing such challenges is the rapid development of educational tools that use artificial intelligence, such as ChatGPT, Gemini, and similar platforms. Although these tools can help improve the learning process, there are also risks if they are used improperly. Additionally, we should be grateful that many students in Indonesia still uphold academic integrity. This is evident from the ease of finding participants for this study, which aims to uncover the psychological and social factors that encourage ethical behavior. This study uses the Theory of Planned Behavior to investigate the extent to which Attitudes Toward Behavior (ATB), Subjective Norms (SN), and Perceived Behavioral Control (PBC) influence a student's Behavioral Intentions (BI), as well as how those intentions translate into Actual Behavior (AB). Using a purposive sampling method involving 300 students from various regions in Indonesia, the data were analyzed through Structural Equation Modeling (SEM) using AMOS software. The results of the study show that ATB, SN, and PBC each have a positive and significant influence on BI, which then strongly predicts AB. These findings can help to better understand the mechanisms behind academic honesty and provide practical suggestions for designing programs that strengthen ethical behavior in an increasingly digital learning environment.